Zinc Oxide Nanowires Exposure Induces a Distinct Inflammatory Response via CCL11-Mediated Eosinophil Recruitment - Alghsham, Ruqaih S.; Satpathy, Shuchismita R.; Bodduluri, Sobha R.; Hegde, Bindu; Jala, Venkatakrishna R.; Twal, Waleed; Burlison, Joseph A.; Sunkara, Mahendra; Haribabu, Bodduluri (Frontiers in Immunology, 2019)
High aspect ratio zinc oxide nanowires (ZnONWs) have become one of the most important products in nanotechnology. The wide range applications of ZnONWs have heightened the need for evaluating the risks and biological consequences to these particles. In this study, we investigated inflammatory pathways activated by ZnONWs in cultured cells as well as the consequences of systemic exposure in mouse models. Confocal microscopy showed rapid phagocytic uptake of FITC-ZnONWs by macrophages. Exposure of macrophages or lung epithelial cells to ZnONWs induced the production of CCL2 and CCL11. Moreover, ZnONWs exposure induced both IL-6 and TNF-α production only in macrophages but not in LKR13 cells. Intratracheal instillation of ZnONWs in C57BL/6 mice induced a significant increase in the total numbers of immune cells in the broncho alveolar lavage fluid (BALFs) two days after instillation. Macrophages and eosinophils were the predominant cellular infiltrates of ZnONWs exposed mouse lungs. Similar cellular infiltrates were also observed in a mouse air-pouch model. Pro-inflammatory cytokines IL-6 and TNF-α as well as chemokines CCL11, and CCL2 were increased both in BALFs and air-pouch lavage fluids. These results suggest that exposure to ZnONWs may induce distinct inflammatory responses through phagocytic uptake and formation of soluble Zn2+ ions.